2005
DOI: 10.1111/j.1439-0396.2005.00611_8.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐laminitic metabolic syndrome in genetically predisposed ponies involves compensated insulin resistance

Abstract: Adaptation to diets which replace carbohydrates with fat as an energy source have been shown to avoid insulin resistance and improve metabolic regulation during exercise. This study compared the effects of diet and moderate-intensity exercise on glucose and insulin concentrations in 12 trained Arabian geldings. Six Arabians were adapted for 8 weeks to a feed high AAVN Abstracts 2005 Reference Appel, L. J., 2000 The role of diet in the prevention and treatment of hypertension. Current Atherosclerosis Reports 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
8
2
Order By: Relevance
“…Although the serum insulin concentrations achieved in this study were higher than those commonly associated with equine Cushing's disease (McGowan et al. 2004), or those reported with some cases of pasture‐associated, endocrinopathic laminitis (Treiber et al. 2005), concentrations >1000 µ iu/ml have occasionally been reported in the field (Reeves et al.…”
Section: Discussioncontrasting
confidence: 61%
“…Although the serum insulin concentrations achieved in this study were higher than those commonly associated with equine Cushing's disease (McGowan et al. 2004), or those reported with some cases of pasture‐associated, endocrinopathic laminitis (Treiber et al. 2005), concentrations >1000 µ iu/ml have occasionally been reported in the field (Reeves et al.…”
Section: Discussioncontrasting
confidence: 61%
“…Several conditions associated with laminitis in horses, such as equine Cushing's syndrome (pituitary pars intermedia dysfunction, PPID) (Johnson et al . 2004), equine metabolic syndrome (Johnson 2002; Treiber et al . 2005) and iatrogenic corticosteroid administration (Johnson et al .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged administration of insulin to induce hyperinsulinaemia while maintaining normal glucose concentrations resulted in the development of clinical and histological laminitis in all 4 feet of healthy ponies within 72 h and of healthy Standardbred horses within 48 h suggesting that IR and the associated hyperinsulinaemia place horses and ponies at risk of developing laminitis through direct insulin toxicity. However, it must be acknowledged that the serum insulin concentrations achieved in these studies were much higher than those commonly associated with PPID and those reported in some cases of pasture‐associated, endocrinopathic laminitis and similarly high serum insulin concentrations have been documented in recurrently laminitic ponies in the absence of clinical signs of laminitis such that very high serum insulin concentrations alone are not necessarily laminitis‐inducing. In addition, subsequent histological examination of the laminitis lesions from the ponies with experimental insulin‐induced laminitis revealed a lack of widespread basement membrane disintegration and instead the predominant lesion was one of apoptosis and mitosis in the axial regions .…”
mentioning
confidence: 64%